The Effect of Curriculum Management and Local Wisdom-based Learning on Student Learning Outcomes at SMA NEGERI 2 SERAM BARAT - Kempa, R.; Sohilait, Desembra (KnE Social Sciences, 2024)
This study aims to determine the effect of curriculum management and local wisdom-based learning on student learning outcomes at SMA Negeri 2 Seram Bagian Barat. In this study, researchers used quantitative methods. The participants of this study were 10% of the 350 students at SMA Negeri 2 SBB and the researchers got 35 students. The data collection was done using a questionnaire. Data analysis used were percentage and multiple linear regression to see the significant influence of curriculum management variables (X1) and local wisdom-based learning (X2) on the learning outcomes variable (Y) of students at SMA Negeri 2 SBB in the 2023/2024 academic year. Based on the calculation results, it is known that the significance value is 0.788. This means that the significance value (0.788) > 0.05, so it can be concluded that the influence of curriculum management (X1) and local wisdom (X2) had no effect on learning outcomes (Y). Keywords: curriculum management, local wisdom, learning result